Dual-targeting and microenvironment-responsive micelles as a gene delivery system to improve the sensitivity of glioma to radiotherapy - Xiuxiu Jiao; Yuan Yu; Jianxia Meng; Mei He; Charles Jian Zhang; Wenqian Geng; Baoyue Ding; Zhuo Wang; Xueying Ding (Elsevier, 2019)
Dbait is a small double-stranded DNA molecule that has been utilized as a radiosensitizer to enhance the sensitivity of glioma to radiotherapy (RT). However, there is no effective drug delivery system to effectively overcome the bloodbrain barrier (BBB). The aim of this study was to develop a gene delivery system by using the BBB and glioma dual-targeting and microenvironment-responsive micelles (ch-Kn(s-s)R8-An) to deliver Dbait into glioma for RT. Angiopep-2 can target the low-density lipoprotein receptor-related protein-1 (LRP1) that is overexpressed on brain capillary endothelial cells (BCECs) and glioma cells. In particular, due to upregulated matrix metalloproteinase 2 (MMP-2) in the tumor microenvironment, we utilized MMP-2-responsive peptides as the enzymatically degradable linkers to conjugate angiopep-2. The results showed that ch-Kn(s-s)R8-An micelles maintained a reasonable size (80-160 nm) with a moderate distribution and a decreased mean diameter from the cross-linking as well as exhibited low critical micelle concentration (CMC) with positive surface charge, ranging from 15 to 40 mV. The ch-K5(s-s)R8-An/pEGFP showed high gene transfection efficiency in vitro, improved uptake in glioma cells and good biocompatibility in vitro and in vivo. In addition, the combination of ch-K5(s-s)R8-An/Dbait with RT significantly inhibited the growth of U251 cells in vitro. Thus, ch-K5(s-s)R8-An/Dbait may prove to be a promising gene delivery system to target glioma and enhance the efficacy of RT on U251 cells. KEY WORDS: Glioma-targeting, Cell-penetrating peptides, Microenvironment-responsive micelles, Gene delivery, Radiosensitizer